Occurrence of Philometra lateolabracis (Nematoda: Philometridae) in the gonads of marine perciform fishes in the Mediterranean region - Moravec, Frantisek; Glamuzina, Branko; Marino, Giovanna; Merella, Paolo; Di Cave, David (Diseases of aquatic organisms, 2003)
Gravid females of the nematode Philometra lateolabracis (Yamaguti, 1935), a parasite of gonads of marine perciform fishes, were found in wild and cultured dusky grouper Epinephelus marginatus (Lowe) from waters near the Balear Islands (Spain, Mediterranean Sea) and Sicily (Italy, Thyrrenean Sea), and in the greater amberjack Seriola dumerili (Risso) in Croatia (south-eastern Adriatic Sea). In wild E. marginatus in Spain, the overall prevalence was 21% and the intensity of infection 1 nematode per fish. The nematodes are briefly described and illustrated. The species Sanguinofilaria jordanoi López-Neyra, 1951, described from the ovary of Epinephelus gigas Brünich from Morocco, is synonymized with P. lateolabracis. This is the first documented record of P. lateolabracis from fishes of the Mediterranean region and its finding in S. dumerili represents a new host record. The possible importance of this pathogenic parasite for cultures of marine perciform fishes in the region is stressed.
Keywords: Středomoří; Gonads; Female; Prevalence; Dracunculoidea; nemoci ryb; Mediterranean Sea; infekce hlísticemi řádu Spirurida; Animals; Středozemní moře; Mediterranean Region; ženské pohlaví; gonády; zvířata; Spirurida Infections; Perciformes; Fish Diseases; prevalence